The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1524-4725.2004.30376.x
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastasis of a Sentinel Lymph Node in Cutaneous Melanoma Is a Significant Prognostic Factor for Disease-Free Survival, Distant-Metastasis-Free Survival, and Overall Survival

Abstract: The study examined patients with melanomas of all tumor thicknesses and SLNB for which the prognostic significance of SLNB was tested. Recurrences were more frequent in patients with a micrometastatic SLN. Patients with a negative SNLB are still at risk for tumor recurrence. The histopathologic result of SLNB is, after tumor thickness, the most significant prognostic factor for disease-free survival, distant-metastasis-free survival, and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…The results in this study are only valid for patients without information of SNB or patients with a negative SNB. A positive SNB significantly increases the risk of recurrence . A recent large population‐based study from Sweden also showed that the risk of dying from CMM was three times higher after a positive SNB compared to a negative SNB …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results in this study are only valid for patients without information of SNB or patients with a negative SNB. A positive SNB significantly increases the risk of recurrence . A recent large population‐based study from Sweden also showed that the risk of dying from CMM was three times higher after a positive SNB compared to a negative SNB …”
Section: Discussionmentioning
confidence: 99%
“…A worse prognosis in patients with localized primary CMM is related to increasing age, male sex, nodular histogenetic type, increasing tumour thickness, presence of tumour ulceration and also presence of mitoses in T1 CMM . However, few studies have used multivariable analyses to identify prognostic risk factors for first recurrence, including locoregional and distant metastases in stages I‐II CMM patients . Most previous studies have used selected hospital‐based data, but only one has used population‐based data .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S‐classification is highly reliable with the prediction of positivity of non‐SLNs and clinical outcome with S0 and SI being the most favorable groups. Other studies have also demonstrated that micrometastasis in melanoma SLNs is clinically significant 15–22. In a prospective randomized Multicenter Selective Lymphadenectomy Trial I, 1,269 patients with primary cutaneous melanoma were randomized to wide excision and observation with lymph node dissection of the nodal basin only when recurrence was noted in the nodal basin versus wide excision and selective sentinel lymphadenectomy followed by completion lymph node dissection when the SLNs were positive.…”
Section: Sln Micrometastasis and Clinical Outcome In Melanomamentioning
confidence: 99%
“…Due to its direct lymphatic connection with the primary tumor, the SLN will most probably filter the first tumor cells to metastasize via lymphatics. The presence or absence of lymph node metastases is one of the most significant prognostic factors for melanoma patients, underscoring the importance of diagnostic lymphadenectomy [2–4]. Numerous studies have shown that the selective dissection of the SLN allows more accurate tumor staging in melanoma [2, 5–7].…”
Section: Introductionmentioning
confidence: 99%